Analog switch-off (ASO) effect in brand image of TV one as election TV ahead of the political year on viewers' watching interest in Jakarta - Tysa Novenny; Muchsin Saggaff Shihab (Sean Institute, 2024)
Stations that are synonymous with political news will certainly be affected by the presence of ANALOG SWITCH-OFF. One of the most popular TV stations synonymous with political issues is TV One. In November 2022, TV One will hold a launch event for TV One as Election TV. The launch event which was attended by a number of figures from political parties, the chairman of the KPU, and the chairman of Bawaslu further emphasized TV One's brand image as Election TV. Research methods This using the type and design of a quantitative research approach. This research uses a stratified random sampling technique. The data used is 2022 data sourced from the DKI Jakarta Provincial Central Statistics Agency. Amount sample determined based on Slovin formula totaling 400 respondents. Result of study This show that h smartPLS calculation results which state the direct influence between variables. If the P-Value is <0.05, then there is an influence between variables the analogous switch-off effect in brand image on interest watch viewers in Jakarta